Educational Big Data Initiates a New Era in Education Development - Yang, Yaodong (Science Insights Education Frontiers, 2024)
Over the past more than ten years, big data technology has posed profound impacts to almost all sectors including education. This state-of-the-art technology prompts changes in educational notions, pedagogy, and the roles of teachers and students. Educational big data proliferates with the improvement of school digital infrastructure, popularization of campus networks, increase in educational applications, widespread use of learning management systems (LMS) and other terminal devices (Chaurasia & Rosin, 2017). There is a consensus among researchers that judicious exploitation of educational big data is beneficial for optimizing education resource distribution, reaching scientific educational decisions, and elevating the quality of instruction (Cui, 2023). The benefits of big data application in education have also been well recognized by educators; schools and other education institutions are increasing endeavors to integrate big data technology into instruction.